Implementation of Strategic Management in Educational Institutions: Its Impact on Teacher Professionalism - Yuli Eka Purwanti; Erny Roesminingsih; Karwanto Karwanto (Universitas Teuku Umar, 2025)
This study aims to analyze the implementation of strategic management based on Wheelen and Hunger's theory in educational institutions and evaluate its impact on teacher professionalism. The method used is a literature study that examines various recent journals from 2015 to 2025 that are relevant to strategic management, education, and educator professionalism. The results showed that the implementation of the four main phases of strategic management-environmental scanning, strategy formulation, implementation, and evaluation and control-contributed significantly to improving organizational quality and teacher professionalism. In addition, the involvement of all stakeholders and effective leadership support the success of the strategy and the development of educators' academic and social competencies. The main conclusion shows that the systematic and participatory implementation of strategic management can strengthen educators' professionalism and improve the overall quality of education. This research confirms the importance of integrating strategic management theory in education management to achieve sustainability and improve the quality of teaching and learnin